Advocating for Medicaid Expansion in Republican States: Overcoming "Fractious Federalism" in the Statehouse and Ballot Box. Issue 3 (24th July 2021) - Haselswerdt, Jake
Abstract: Partisan and ideological polarization have been major barriers to the implementation of the Affordable Care Act's Medicaid expansion in Republican-controlled states. Scholars have referred to this situation as "fractious federalism, " with Republican state policymakers toeing the national party line in refusing to cooperate with a major policy initiative. In some cases, however, diverse advocacy coalitions have overcome fractious federalism to pass expansion legislation in deeply Republican states. More recently, such coalitions have resorted to ballot initiative campaigns as another means of overcoming such polarization, and won impressive victories in a series of "deep red" states. Drawing on forty-four interviews with people involved in expansion advocacy in eleven states, I report important insights on the formation and activities of these coalitions in both the legislative and ballot initiative eras of Medicaid expansion politics.